Penambahan Molases Untuk Meningkatkan Kualitas Amoniasi Jerami Padi dan Pengaruhnya terhadap Produk Fermentasi Rumen Secara In-Vitro - Muhamad Bata; Nur Hidayat (Jurnal Agripet, 2010)
Supplementation of molasses to improve the quality of rice straw ammonization and its effect on fermentation product in-vitro